The Concept of Evil in African Communities: The Case of the Yoruba, Akan and Igbo People - Godfred Adjei Nyarko (Noyam Publishers, 2021)
Traditionally, Africans see themselves as each other’s keeper, and that is the main reason for the concern shown towards each other and the general wellbeing of all in society. Africans do not talk about individualism because it contradicts the traditional African understanding of family, traditional practices, beliefs and values that seek to create a society that will be free from the effect of evil. Despite this communal co-existence to create a peaceful society, there are violations of the moral order through the employment of mystical powers to harm others. The belief in the presence of mystical powers that work against the progress of others has influenced the cultural, religious and daily lives of the people, bringing into question the role of the Supreme Being in all these. The use of these mystical powers to impede people’s wellbeing is unacceptable in African thought. The paper discusses metaphysics and contemporary philosophy about the problem of evil and how it influences human actions. It has also conceptually and comparatively explored the notion of evil in Akan, Yoruba and Igbo communities within the African ethos. Again, it seeks to give exposition on some African notions of evil, from the understanding that evil is not the creation of God but results from the actions of humanity. The proposition of this paper is that most African communities do not perceive the existence of evil as a sufficient reason to discredit the existence of God, the Supreme Being.